Appearance-related concerns in individuals with pathological skin picking - a comparison with individuals with dermatological conditions and skin-healthy controls - Schmidt, Jennifer; Gallinat, Christina; Martin, Alexandra (Frontiers in medicine, 2023)
IntroductionPathological skin picking (PSP) is an excessive behavior which characterizes Skin Picking Disorder. Individuals repeatedly pick their skin and cause skin lesions, but are unable to control the behavior, which can cause severe distress. Visible self-inflicted skin lesions can additionally affect individuals with PSP due to emerging appearance-related concerns. However, these concerns and their role in PSP have hardly been studied, especially not in comparison with individuals with dermatological conditions and skin-healthy controls.MethodsThe present cross-sectional study (n = 453, 83.9% female, 15.9% male, 0.2% diverse) aimed at analyzing appearance-related concerns and mental health outcomes between four groups: Individuals with PSP and dermatological conditions (SP/DC; n = 83), PSP without dermatological conditions (SP; n = 56), dermatological conditions without PSP (DC; n = 176) and skin-healthy controls (SH, n = 138). We compared questionnaire data on dysmorphic concerns, appearance-based rejection sensitivity, and body dysmorphic symptoms, as well as PSP-symptoms and mental health outcomes (depression, anxiety, and self-esteem) between groups.ResultsThe analyses showed a significant multivariate group effect in the appearance-related variables, F(6, 896) = 19.92, Wilks’ Λ = 0.78, p < 0.001, and mental health outcomes, F(6, 896) = 16.24, Wilks’ Λ = 0.81, p < 0.001. The SP/DC group had the strongest appearance-related concerns and mental health impairments, followed by the SP group, the DC group and the SH group. The SP/DC group and SP group only differed significantly with regard to dysmorphic concerns, but not in other variables. The DC group was less affected but still showed higher dysmorphic concerns and mental health impairments than skin-healthy controls. In contrast to the PSP groups, the other two groups did not exceed clinically relevant cut-off scores.DiscussionThe present study shows that individuals with PSP exhibit strong appearance-related concerns, regardless of the presence or absence of underlying or comorbid dermatological conditions. These findings shed new light on the importance of appearance-related concerns in Skin Picking Disorder and the role of PSP as a potentially overlooked risk factor in dermatological patients. Therefore, appearance-related concerns should be explicitly addressed in dermatological and psychotherapeutic settings. Future studies should also include longitudinal and experimental analyses to more clearly classify the role of appearance-related concerns in the etiology of PSP and Skin Picking Disorder.
Gesehen am 19.06.2023